2018
DOI: 10.1111/rec.12855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating outcomes of restoration ecology projects on limited budgets: assessment of variation in sampling intensity and sampling frequency for four habitat types

Abstract: While best practices for evaluating restoration ecology projects are emerging rapidly, budget constraints often limit postrestoration monitoring, which emphasizes the need for practical and efficient monitoring strategies. We examined the postrestoration outcome for an ENGO (Nature Conservancy of Canada) project, to assess retroactively how variation in intensity and frequency of sampling would have affected estimates of plant species composition, diversity, and richness over time. The project restored four ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(57 reference statements)
0
2
1
Order By: Relevance
“…While some studies have found that species composition can stabilize a few years following restoration (Henry et al, 2019; Stuble et al, 2017), our study demonstrates that functional composition can change across microhabitats and over time, at least in our woody‐dominated communities. For example, more stressful microhabitats, such as our south‐facing slopes, may require more management due to lower initial cover (i.e., weeding) early in a restoration project, but planting species with resource conservative traits may lead to increased cover over time.…”
Section: Discussioncontrasting
confidence: 55%
“…While some studies have found that species composition can stabilize a few years following restoration (Henry et al, 2019; Stuble et al, 2017), our study demonstrates that functional composition can change across microhabitats and over time, at least in our woody‐dominated communities. For example, more stressful microhabitats, such as our south‐facing slopes, may require more management due to lower initial cover (i.e., weeding) early in a restoration project, but planting species with resource conservative traits may lead to increased cover over time.…”
Section: Discussioncontrasting
confidence: 55%
“…Defining restoration outcomes is nontrivial and will continue to be a challenge (Diefenderfer et al ; Svejcar & Kildisheva ; Gellie et al ; Henry et al ). Several novel thinking themes were proposed at the meeting.…”
Section: Strategic Issuesmentioning
confidence: 99%
“…Most studies assessing the role of sampling intensity for restoration success target vascular plants (e.g. Viani et al ; Henry et al ); we are unaware of any study that has examined the effect of sampling intensity on assessments of restoration success using insect bioindicators.…”
Section: Introductionmentioning
confidence: 99%